Stratigraphy and 40Ar/39Ar geochronology of the Santa Rosa basin, Baja California: Dynamic evolution of a constrictional rift basin during oblique extension in the Gulf of California. (20th March 2013) - Seiler, C.; Quigley, M.C.; Fletcher, J.M.; Phillips, D.; Gleadow, A.J.W.; Kohn, B.P.
Abstract The Santa Rosa basin of northeastern Baja California is one of several transtensional basins that formed during Neogene oblique opening of the Gulf of California. The basin comprises Late Miocene to Pleistocene sedimentary and volcanic strata that define an asymmetric half‐graben above the Santa Rosa detachment, a low‐angle normal fault with ca. 4–5 km of SE‐directed displacement. Stratigraphic analysis reveals systematic basin‐scale facies variations both parallel and across the basin. The basin‐fill exhibits an overall fining‐upward cycle, from conglomerate and breccia at the base to alternating sandstone‐mudstone in the depocentre, which interfingers with the fault‐scarp facies of the detachment. Sediment dispersal was transverse‐dominated and occurred through coalescing alluvial fans from the immediate hanging wall and/or footwall of the detachment. Different stratigraphic sections reveal important lateral facies variations that correlate with major corrugations of the detachment fault. The latter represent extension‐parallel folds that formed largely in response to the ca. N‐S constrictional strain regime of the transtensional plate boundary. The upward vertical deflection associated with antiformal folding dampened subsidence in the northeastern Santa Rosa basin, and resulted in steep topographic gradients with a high influx of coarse conglomerate here. By contrast, the downward motion in the synform hinge resulted in increased subsidence, and led to a southwestward migration of the depocentre with time. Thus, the Santa Rosa basin represents a new type of transtensional rift basin in which oblique extension is partitioned between diffuse constriction and discrete normal faulting. 40Ar/39Ar geochronology of intercalated volcanic rocks suggests that transtensional deformation began during the Late Miocene, between 9.36 ± 0.14 Ma and 6.78 ± 0.12 Ma, and confirms previous results from low‐temperature thermochronology (Seiler et al., 2011). Two other volcanic units that appear to be part of a conformable syn‐rift sequence are, in fact, duplicates of pre‐rift volcanics and represent allochthonous, gravity‐driven slide blocks that originated from the hanging wall.